Loyalty Within the Dynamics of Compensation and Career Development Through the Role of Social Support for Innovative Employees at Bank Muamalat Regional East Java - Nuha, Mochammad Syafi'udin; Mardani , Ronny Malavia; Basalamah, Muhammad Ridwan (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of compensation and career development on employee loyalty, with social support as an intervening variable in innovative employees at Bank Muamalat Regional East Java. This study uses a quantitative approach with survey methods and simple random sampling techniques. The sample used was 100 respondents from six branch offices, and data were collected using a Likert scale questionnaire. Data analysis was carried out using the Structural Equation Modeling (SEM) approach using the AMOS program. The validity test used Confirmatory Factor Analysis (CFA), while reliability was measured through construct reliability and variance extracted values with cut-off values > 0.70 and > 0.50. The research model was declared feasible based on Goodness-of-Fit values such as CMIN/DF, GFI, TLI, RMSEA, and CFI which were within acceptable criteria. The results of the tests showed that career development had a significant positive effect on loyalty and social support, while compensation only had a significant effect on social support, but not on loyalty. Social support has no significant effect on loyalty, nor does it mediate compensation or career development relationships on loyalty. These findings confirm that in the context of Islamic banking, especially at Bank Muamalat, employee loyalty is more influenced by value approaches and spiritual aspects than mere material incentives or social climate. Therefore, human resource management strategies need to strengthen value integration, spirituality-based development, and create a more structured support system